Proceedings of the International Health Informatics Conference IHIC 2022 - Jain, Sarika; Groppe, Sven.; Mihindukulasooriya, Nandana (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book will constitute the proceedings of the International Health Informatics Conference (IHIC 2022). This volume focus on artificial intelligence, machine learning, and deep learning approach with their automated intelligent cognitive knowledge as an assisting tool to the existing healthcare tools. The topics covered in this volume are data mining, patient electronic health records, healthcare portals, telemedicine, automatic identification and data collector systems, RFID and localization techniques, usability and ubiquity in e-Health, artificial intelligence for healthcare decision-making, etc. This volume will prove a valuable resource for those in academia and industry.
Development of Health Care System using Soft Computing Methods -- A Novel Yoga Based Practice Protocol to Quantify Stress after Performing Attention Task using Non-Invasive Techniques -- A Study of Deep Learning Algorithms in Sentiment Analysis of Diverse Domain -- Frequency Allocation in Cognitive Radio Networks -- An IoT Based Advanced Health Monitoring System -- Fault Tolerance in Vehicular Cloud Networks: Link Failure and Malicious Node Detection and Reconfiguration -- Multifilter Enhanced Doctor and Patient Optimization Algorithm for Cancer Diagnosis -- Disease Diagnostic Model using Fine-Tuned Intensive Learning for Medical Image -- Challenges in Digital Health Care- A Hybrid Decision Approach Understanding Key Challenges in India -- Telemedicine and Healthcare Setting for Remote Care of Patients: Status and Future Implications -- Performance Evaluation of ML Models in the Health Care Domain to Classify Liver Disease: A Case Study.
Keywords: Application software; Computational intelligence; Artificial intelligence; Quantitative research; Computer and Information Systems Applications; Computational Intelligence; Artificial Intelligence; Data Analysis and Big Data